Law in Diplomacy - Corbett, Percy Ellwood (Princeton, NJ : Princeton University Press, 2015)
In this lively and informative volume Professor Corbett examines the role of law in the relations of nations, focusing on American, British, and Russian diplomacy. In case studies from 1585 to 1958 he considers the reasons why nations appeal to universal norms, traces the growth of a distinct body of rules appropriate to intergovernmental affairs, and assesses the influence of legal notions on foreign policy.Originally published in 1959.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- FOREWORD -- PREFACE -- ACKNOWLEDGMENTS -- CONTENTS -- ABBREVIATIONS -- CHAPTER I. BRITAIN AND ITS L AW OF NATIONS -- CHAPTER 2. ENTER T H E UNITED STATES -- CHAPTER 3. THE SOVIET DILEMMA -- CHAPTER 4. MARE LIBERUM AND MARE CLAUSUM -- CHAPTER 5. THE DIPLOMACY OF ARBITRATION -- CHAPTER 6. INTERNATIONAL ORGANIZATION -- CHAPTER 7. HUMAN RIGHTS AND WORLD COMMUNITY -- CHAPTER 8. CONCLUSIONS -- INDEX
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: Diplomacy; International law; International relations; POLITICAL SCIENCE / International Relations / Diplomacy